The sayyids of Perak: a preliminary study on their origins and influences in the Perak society - Sulkafle, Mohamad Hazizie (History Department, University of Malaya, 2020)
This article would like to highlight one sayyids family which for a long time had been marginal in the academic world – the Sayyids of Jamalullail of Perak. This article argues that they have contributed significantly to the Islamisation and the administration of the Perak Sultanate since its establishment in the early 16th century until the early 20th century, particularly through their position as Orang Kaya Menteri Paduka Tuan for several generations. Hence, utilizing several manuscripts available in the National Archive of Malaysia and the SOAS Digital Collections, and supported by other relevant sources, their origins and contributions to the Perak Sultanate will be discussed and highlighted accordingly. Even at one time, these sayyids dominated Orang Besar Empat offices of the Perak Sultanate, except Temenggung. As Orang Kaya Menteri Paduka Tuan who is in charge of religious matters, these Sayyids compiled a set of laws known as the Ninety-nine Laws of Perak which signify an intellectual legacy of the Malay society. This set of laws is important in understanding the Islamisation process and the interactions between Islam and adat in Malay society.